China's R&D explosion: Analyzing productivity effects across ownership types and over time - Philipp Boeing; Elisabeth Mueller; Philipp Sandner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
In the past years Chinese firms increased their spending on R&D substantially and worked on achieving a higher quality level of R&D. We analyze whether different R&D activities show a positive influence on total factor productivity (TFP) for firms of different ownership types and across two time periods. Our panel dataset with annual information allows us to study listed firms over the two time periods 2001-2006 and 2007-2011. Privately owned enterprises (POEs) not only obtain higher returns from own R&D than majority and minority state-owned enterprises (SOEs), they are also able to increase their leading position. Overall strong increases in the size of patent stocks are related to a decreasingly positive or even vanishing influence on TFP. POEs not only produce R&D of the highest quality but are also the only ownership type profiting from higher quality. Up to now research collaborations allow almost no benefit with the only exception stemming from domestic collaborations with individuals. Our comprehensive analysis depicts strengths but also weaknesses of the corporate sector in China. We derive implications for the further development of economic policies.
urn:nbn:de:bsz:180-madoc-387494
Keywords: O32; O33; 330; productivity; R&D; China; ownership type; patents